ANALISIS PARTISIPASI MASYARAKAT DALAM PEMANFAATAN LAYANAN PUBLIK BERBASIS DIGITAL UNTUK MEWUJUDKAN GOOD GOVERNANCE DI KECAMATAN MEDAN TIMUR - Karina Alexandra; Artha Tobing; Dimpos Manalu; Jonson Rajagukguk (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The development of information technology encourages governments to transform public services through the implementation of digital-based services as an effort to realize good governance. The digitalization of public services at the sub-district level is expected to enhance transparency, accountability, and provide wider opportunities for public participation. However, the utilization of digital-based public services in Medan Timur Sub-district has not been fully optimal, as some members of the community still prefer face-to-face services rather than using the digital platforms that have been provided. This study aims to analyze the forms of community participation in utilizing digital-based public services in Medan Timur Sub-district and to identify the supporting and inhibiting factors of such participation in realizing good governance. This research employs a qualitative method with a descriptive approach. Data were collected through interviews with key informants, main informants, and additional informants, supported by documentation studies. The data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing based on the Miles and Huberman model. The results of the study indicate that community participation in digital-based public services in Medan Timur Sub-district is still at a consultative level, which is reflected through the utilization of services such as complaint platforms, access to administrative information, and the Digital Population Identity (IKD) service. Digital services have also supported transparency through information openness and strengthened accountability through digital recording systems and documented complaint mechanisms. The supporting factors of community participation include the availability of digital platforms, the responsiveness of government officials, and documented service systems. Meanwhile, the inhibiting factors include low levels of digital literacy among some members of the community, limited access to devices and internet connectivity, and the community’s preference for direct face-to-face services.